Peran Penatua Gereja dalam Pembinaan Iman Pemuda di GKPI Martoba Medan - Anita Yohanna Manurung; Nurliani Siregar; Justinos Ray Nainggolan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the role of church elders in the spiritual formation of youth at GKPI Martoba Medan. The background of this research is the increasing challenges faced by young people in maintaining their faith due to modern lifestyle, social media influence, and lack of spiritual guidance. This research uses a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The results show that church elders play an important role in strengthening the youth’s faith through activities such as Bible Study, retreats, outdoor worship, and youth involvement in church programs. Elders serve as mentors, motivators, and role models for the spiritual growth of young people. The main challenges include low interest in spiritual activities, strong social media influence, and the rise of secular and hedonistic mindsets. To address these challenges, elders build closer relationships with youth, provide relevant teachings, and encourage youth participation in various ministries. The study concludes that spiritual formation will be more effective when elders, the church, and youth work together to build strong and sustainable faith development